Odpowiedzi

Najlepsza Odpowiedź!
2010-03-03T15:01:01+01:00
A) 4x-3=3x+5
4x-3x=5+3
x=8

b) 5x+2=7-3x
5x+3x=7-2
8x=5/przez 8
x= 5/8

c) 3(x-1)=0
3x-3=0
3x=3/3
x=1

d) -6(x+1)=24
-6x-6=24
-6x=30/(-6)
x= -5

e) -7(x-2)=3x-1
-7x+14=3x-1
-7x-3x = -1-14
10x=-15 /(-10)
x= 15/10 po skróceniu przez 5 =3/2= m1i 1/2

f) 4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10/*(-2)
x=-5


2) Rozwiąż równania.
a) 0,2x+0,3= -0,5
0,2x=-0,5-0,3
0,2x=-0,8/0,2
x=4


b) 0,4+0,25x= -2
0,25x=-2-0,4
0,25x=-2,4/0,25
x=-9,6

c) 2,1-0,3x=0,4x
-0,3x-0,4x=-2,1
-0,7x=-2,1/(-0,7)
x=3